Stan religijno-moralny parafii rzymskokatolickiej w Szadku w drugiej połowie XVIII w. Miejsca kultu, duszpasterze, parafianie - Rulka, Kazimierz (Biuletyn Szadkowski, 2013)
The inhabitants of Szadek and its neighbourhood, gathering in the parish church to participate in the liturgy and listen to the Church teaching, shaped their religious and moral attitudes. The source materials providing the basis for establishing the religious and moral state of the parish of Szadek in the second half of the 18th century include primarily the preserved records of five canonical inspections carried out in 1759-1760, 1762, 1779, 1788 and 1798. The Worship of God Was mainly performed during services and masses in three churches: the parish church under the invocation of the Assumption of the Holy Virgin and St. James the Apostle, renovated in 1788, With rich interior decorations (13 altars, many paintings and sculptures), St. Giles’ Church, also renovated in 1788 and used only occasionally, and the Holy Trinity Church at the local hospital. The religious and moral condition of the parishioners depended largely on the parish clergy - their personal attitude and pastoral care. In the first half of the 18th century, the person responsible for pastoral Work Was the local parish-priest, supported by the missionary college priests (performing also other functions in the parish) and the hospital provost. The parishioners themselves took active part in the religious and moral formation of their community through activities of church brotherhoods, guilds and a parish school, as Well as in the care for the sick, elderly, poor and homeless (the hospital, fulfilling also the function of a poor-house).